Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

$P$ is probability. We have: $P(A) \ge \frac{2}{3}$, $P(B) \ge \frac{2}{3}$, $P(C) \ge \frac{2}{3}$ and $P(A \cap B \cap C)=0$. We have to find $P(A)$. How to do it? Of course we have $P(A \cup B \cup C) = P(A) + P(B) + P(C) - P(A \cap B)- P(A \cap C)- P(B \cap C)$, but what next? Please, help me.

share|improve this question

2 Answers 2

up vote 2 down vote accepted

Hints:

  • If $\mathbb P(B)\geqslant\frac23$ and $\mathbb P(C)\geqslant\frac23$, then $\mathbb P(B\cap C)\geqslant$ $____$.
  • If $\mathbb P(A)=\frac23+c$ with $c\gt0$ and $\mathbb P(B\cap C)\geqslant$ $____$, then $\mathbb P(A\cap(B\cap C))\geqslant$ $____$.
  • But the hypothesis is that $\mathbb P(A\cap B\cap C)=0$, hence $\mathbb P(A)=\frac23$.
share|improve this answer

First, observe that

$$P(X \cap Y) = 0 \text{ implies } P(X \cap Y^c) = P(X). \tag{1}$$

Then, bound $P(B \cap C)$ by $$ P(B \cap C) = P(B) + P(C) - P(B \cup C) \geq 2\frac{2}{3}-1 = \frac{1}{3}.$$

Finally, apply $(1)$ to $P(A\cap (B \cap C)) = 0$ to get $$P(A) = P(A \cap (B \cap C)^c) \leq \frac{2}{3}.$$

Concluding, $P(A) = \frac{2}{3}$.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.